Effect of substrate load on anaerobic fermentation of rice straw with rumen liquid as inoculum Hydrolysis and acidogenesis efficiency, enzymatic activities and rumen bacterial community structure - Liang, Jinsong (Waste management (New York, N.Y.), 2021)
Copyright © 2021 Elsevier Ltd. All rights reserved.